A first-principles study of Li and Na co-decorated T4, 4, 4-graphyne for hydrogen storage. (11th February 2021) - Wu, Qiang; Shi, Mingmin; Huang, Xin; Meng, Zhaoshun; Wang, Yunhui; Yang, Zhihong
Abstract: To obtain high hydrogen storage performance, Li and Na co-decorated T4, 4, 4-graphyne have been studied by the method of first-principles calculations in this paper. Li and Na atoms are bound on hexagonal ring and acetylenic ring included in T4, 4, 4-graphyne, with the average adsorption energy of 1.73 and 2.38 eV, respectively. Our calculations show that the maximum gravimetric density of H2 uptake is 10.46 wt%, and an appropriate adsorption energy is reached. Moreover, by plotting charge density differences, it is found that the induced electric field between Li/Na and T4, 4, 4-graphyne can enhance the adsorption for hydrogen molecule. Furthermore, this complex is thermodynamic stable at room temperature, which is certificated by molecule dynamics simulation. Our results demonstrate that Li and Na co-decorated T4, 4, 4-graphyne is an alternative material for hydrogen storage. Highlights: Co-modification of Li and Na atoms can enhance hydrogen storage of T4, 4, 4 -graphyne. The maximum hydrogen storage capacity reaches 10.46 wt%. DFT MD simulation confirms thermodynamic stability of hydrogen storage system.